Treatment outcomes in lower limb lymphedema misdiagnosed as iliac vein compression syndrome: A retrospective analysis - Guijun Huo; Mingqing Du; Zhichao Yao; Dayong Zhou; Zhanao Liu (PLoS ONE, 2025)
Iliac vein compression is highly prevalent in the general population, which may lead to misdiagnosis of lower limb lymphedema as iliac vein compression syndrome and subsequent stent placement. This study retrospectively analyzed the treatment outcomes of 11 patients with secondary lymphedema who had previously been diagnosed with iliac vein compression by venography and underwent iliac vein stenting. Following iliac vein stent placement, six patients with Stage I and IIa lymphedema experienced partial relief of limb swelling; however, symptoms recurred and worsened within three months. The remaining patients showed no improvement in swelling after the stent was placed. Due to inadequate symptom relief following stent implantation, these patients underwent reevaluation and were subsequently diagnosed with lymphedema. Based on disease staging, they received appropriate interventions including complex decongestive therapy, lymphovenous anastomosis, or a combination of liposuction and lymphovenous anastomosis. Four patients with Stage I and IIa lymphedema underwent complex decongestive therapy, four patients with Stage I and IIa lymphedema received lymphovenous anastomosis, and the remaining three patients with Stage IIb lymphedema underwent liposuction combined with secondary lymphovenous anastomosis. Follow-up assessments were conducted at 3, 6, and 12 months post-treatment to evaluate limb morphology and functional outcomes using the Disability and Health Questionnaire for Lower Limb Lymphedema scores. Therapeutic outcomes analysis revealed that complex decongestive therapy, lymphovenous anastomosis, and liposuction demonstrated favorable efficacy in managing lymphedema cases with suboptimal response to prior iliac vein stenting.